POLYLACTIC ACID INTER-CHAIN INTERACTIONS - IRSAI, Izabella; PESEK, Szilárd Zoltán; SILAGHI-DUMITRESCU, Radu (Studia Universitatis Babeș-Bolyai Chemia, 2022)
Geometry optimization of perpendicular, antiparallel and parallel dimers were employed in order to analyze the relative energy values. The weakest interactions are seen for the perpendicular structures; among those, the strongest are for π, 310, while the DeSantis structure affords no local minimum at all. The strongest interactions are seen with parallel structures – of which the largest interaction energies are with the DeSantis and the π monomers (up to 2.8 and 4.2 kcal/mol per unit of lactic acid, respectively).